2013
DOI: 10.1097/rhu.0b013e318289bbbb
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Fibromyalgia in Vasovagal Syncope

Abstract: Fibromyalgia was relatively frequent in these women with vasovagal syncope and could be associated with dysautonomic symptoms. Therefore, it seems important to search for dysautonomic comorbidities in patients with vasovagal syncope and/or fibromyalgia, to provide a patient-centered holistic approach, instead of the often currently used therapeutic partition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Third, we did not compile systematic data on the related confounders which may have had an impact on the miRs expression. These confounders may include different phases of menstrual cycle when patients' blood samples were taken and other comorbidities, such as fibromyalgia, since the latter is associated with syncope (43). Fourth, this study is exploratory in nature and is underpowered to demonstrate associations between miR level and a specific headache profile, such as migraine aura.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we did not compile systematic data on the related confounders which may have had an impact on the miRs expression. These confounders may include different phases of menstrual cycle when patients' blood samples were taken and other comorbidities, such as fibromyalgia, since the latter is associated with syncope (43). Fourth, this study is exploratory in nature and is underpowered to demonstrate associations between miR level and a specific headache profile, such as migraine aura.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, seven additional polymorphisms were included, four of which have participation in cardiovascular physiology 12 and three more SNPs that correlated with fibromyalgia in the Mexican Mestizo population. The reasons behind this choice were 1 the correlation of VVS and ANS dysfunction and the report of the participation of this same dysfunction as a critical element in fibromyalgia 13 , and 2 the description of a positive association of α-AR SNPs with fibromyalgia 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Main studies are described in detail in the next paragraphs. When a study included more than one technique, it was reported only as the first occurrence Instrumental technique Search string Retrieved and selected records Nerve conduction study (fibromyalgia) AND (nerve conduction studies OR electroneurography) Identified 26 Screened 26 Included 5 [ 6 - 11 ] Laser–nociceptive evoked potential or pain-related evoked potentials (fibromyalgia) AND (laser-evoked potentials or LEP or” nociceptive evoked potentials” or “pain related evoked potentials”) Identified 32 Screened 32 Included 9 [ 3 , 12 - 19 ] Autonomic assessment (fibromyalgia) AND ("sympathetic dysfunction" OR "autonomic assessment" OR "heart rate variability" OR "Quantitative Sudomotor Axon Reflex Test" OR “QSART” OR Valsalva OR Tilt test OR Sudoscan OR "sympathetic skin response" OR "SSR" NOT SSR [journal]) Identified 147 Screened 147 Included 10 [ 20 - 29 ] Skin biopsy (fibromyalgia) AND ("skin biopsy" OR small-fiber neuropathy OR "intraepidermal nerve fiber density" OR IENFD) Identified 99 Screened 99 Included 11 [ 17 , 30 - 39 ] Corneal confocal microscopy (fibromyalgia) AND ("corneal confocal microscopy" OR CCM OR "corneal innervation") Identified 14 Screened 14 Included 5 [ 40 - 44 ] Microneurography (fibromyalgia) AND (microneurography) Identified 5 Screened 5 Included 2 [ 45 , 46 ] Quantitative sensory testing (fibromyalgia) AND (quantitative sensory ...…”
Section: Methodsmentioning
confidence: 99%